The Isolation of Antibiotic-Resistant Salmonella from Intestine and Liver of Poultry in Shiraz Province of Iran - Salehi, T. Zahraei; Mahzounieh, M.; Saeedzadeh, A. (International Journal of Poultry Science, 2005)
The aims of this study were to isolation of Salmonella from poultry farms of Shiraz province of Iran and determination of their susceptibility against common antibiotics. One hundred and ninety two samples were harvested from intestine and liver of chickens and were aseptically cultured in enrichment and selective media. Out of 192 samples, 30 Salmonella were isolated. Four different serogroups were found among 30 Salmonella isolates. Strains of serogroup D1, which accounted for 70% of total isolates, were the most common isolates. PCR products of all isolated Salmonella showed a predicted 284 bp amplified DNA fragment of invA gene. All of 30 Salmonella strains were susceptible to the antimicrobial effect of Cephalothin, Tylosin, Colistin, Ciprofloxacin, Enrofloxacin, Gentamicin, Chloramphenicol, Cephalotin and Cefotaxime. But 20.7% of Salmonella strains were resistant to Trimethoprim, Nalidixic acid, Flumequine, Tetracycline and Neomycin, 24.2% to Streptomycin, 34.5% to Kanamycin and 13.8% to Amikacin.